Assessment of Ceratitis capitata (Diptera, Tephritidae) pupae killed by heat or cold as hosts for rearing Spalangia cameroni (Hymenoptera: Pteromalidae) - Tormos, José; Beitia, Francisco J.; Alonso, M.; Asís, Josep D.; Gayubo, Severiano F. (2017)
In this work, we study the suitability of using dead medfly Ceratitis capitata pupae, killed by heat- or cold-shock, for the mass rearing of Spalangia cameroni, a pupal parasitoid of key pests. 100% mortality of medfly pupae could be accomplished with cold-shock at -20 degrees C for 60 min or with heat-shock at 55 degrees C for 30 min. Neither parasitism percentage nor sex ratio of the offspring differed significantly among heat-shocked, cold-shocked and untreated pupae. In addition, there was no significant difference in the percentage of parasitoids that aborted (male male or female female) among pupal treatments. Some of the pupae were covered with peat because the third larval instar of the medfly buries itself before pupation. However, the buried pupae were not parasitised at a greater or lesser rate than those not covered with peat. The percentage of parasitism was also unaffected by whether the pupae had been killed recently or had been stored at between 4 degrees C and 6 degrees C over 15 or 30 days. The use of dead hosts and later storage permitted the following: (a) the use of hosts over long periods of time; (b) a rapid increase in parasitoid numbers and (c) the availability of pupae killed at the most suitable postpupation times for the production of parasitoids. Furthermore, in biological control projects, the use of dead parasitised pupae in the field avoids the risk of enhancing the pest and allows an increase in parasitism in the field through the use of pupae treated with cold- or heat-shock.